The effect of dental restoration geometry and material properties on biomechanical behaviour of a treated molar tooth: A 3D finite element analysis. (January 2022) - Babaei, Behzad; Shouha, Paul; Birman, Victor; Farrar, Paul; Prentice, Leon; Prusty, Gangadhara
Abstract: Objectives: To test the hypothesis that restoration of class II mesio-occlusal-distal (MOD) cavities can be strengthened through judicious choice of restoration geometry and material properties. Methods: An intact extracted human maxillary molar tooth was digitized, segmented, reconstructed, and four 3D restored tooth models were developed with four different restoration geometries: one straight, one single-curved, and two double-curved. Stress analysis was conducted for representative loading using finite element analysis, and maximum principal stresses were determined at the dentine-enamel and restoration-enamel junctions. A range of restorative material elastic moduli (5–80 GPa) and Poisson's ratios (0.25–0.35) were studied. Vertical loads of 400 N were applied on occlusal points, while the roots of the molar teeth, below the crevices, were supported in all directions. All the materials were modelled as homogeneous, isotropic, and elastic. Results: The maximum principal stresses at the restoration-enamel junctions were strongly dependent on the MOD restoration geometries. Peak stresses occurred along the palatal surface of the restoration rather than the opposite buccal surface. Double-curved restorations showed the lowest peak stress at restoration-enamel junctions. Choice of the mechanical properties of restorative material in the range of 5–35 GPa further reduced stress concentrations on the enamel. Significance: Class II MOD restorations may be stronger if designed with double-curved marginal geometries that can reduce stress concentrations. Designs with convex and concave geometries were particularly effective because they reduced stress concentrations dramatically. Results suggest that relatively minor changes to the geometry of a restoration can have a substantial effect on stress at the restoration-enamel junction and motivate future experimental analysis. Graphical abstract: Image 1